Tradition & interpretation - Lennartson, Kari, author; Yust, Dave, 1939-, advisor; Sullivan, Patrice M., advisor; Ellerby, David A., committee member (Colorado State University. Libraries, 2003)
I am of the belief that the human mind is hardwired to create order out of disorder. I begin each work with a rhythmic web of marks, lines, and colors which stretch across the painting surface. It is important to integrate the unexpected into my work: with every misstep which occurs, there is an opportunity to take the image in new directions. As I am interested in creating a varied and complex surface, I work back and forth between the addition and subtraction of materials. I liken my subtractive process to the excavation of earth which an archeologist undergoes when searching for remnants of the past. Thematically, my artwork echoes several motifs found within Old Norse folk art and literature, appeasing a deep yearning for other worlds, remembered and imagined; nostalgia is a potent force within modernism. Motifs utilized include valkyries, telemark skiing, viking longboats, and the spiritual in nature. Archeologist Marie Louise Stig Sorensen relates, "material culture is at the same time active and pliable, meaningful but not absolute." The historical and mythological motifs explored within this body of work recognize the limitations and malleability of interpretation in regards to both Scandinavian historiography and contemporary art. The imagery which emerges from my artistic process owes its inspiration and existence to the initial marks, lines, and colors, and to all of the subsequent layers in between.
Tradition and interpretation
Keywords: mixed media in painting; Painting, American -- 21st century; Mixed media (Art)